The Effect of Therapy of Banana Types of Musa Paradisiaca Var Sapientum Linn on Decreasing Systole and Diastol Blood Pressure in Hypertension Patients - Sudirman Efendi; Nusdin Nusdin; Nur Adelia Arif; Achmad indra Awaluddin (Jurnal Keperawatan, 2023)
Hypertension is a chronic Non-Communicable Disease which is one of the causes due to a lack of potassium intake and high sodium intake. Treatment of hypertension is carried out pharmacologically and non-pharmacologically. One of the non-pharmacological therapies that can help lower blood pressure is to consume bananas of the type musa paradisiaca var sapientum linn because of their high potassium content. This Research  aim  to determine the therapeutic effect of consuming three Ambon bananas (±140 g/fruit) per day for 14 days in reducing diastolic and systolic blood pressure in hypertension sufferers. The research method used was pre-experimental using the One Group Pretest-Posttest design. the sample is hypertension sufferers in the working area of the Pallangga Health Center totaling 16 respondents, selected using purposive sampling technique. The results of the Paired T-Test showed that the p-value of systolic blood pressure = 0.001 and the p-value of diastolic blood pressure = 0.008 (p <0.05), which means that consumption of ambon bananas is effective in reducing systolic and diastolic blood pressure. It can be concluded that there is a significant effect of banana fruit therapy of the type Musa paradisiaca Var Sapientum Linn on reducing systolic and diastolic blood pressure in hypertensive patients. Suggestions from this study are doctors, nurses or other health workers, can provide education to the public regarding the benefits of non-pharmacological therapy in the form of consumption of Ambon bananas for people with hypertension and apply them so that they can be balanced with pharmacological therapy.